2013
DOI: 10.1523/jneurosci.3468-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Chronometric Electrical Stimulation of Right Inferior Frontal Cortex Increases Motor Braking

Abstract: The right inferior frontal cortex (rIFC) is important for stopping responses. Recent research shows that it is also activated when response emission is slowed down when stopping is anticipated. This suggests that rIFC also functions as a goal-driven brake. Here, we investigated the causal role of rIFC in goal-driven braking by using computer-controlled, event-related (chronometric), direct electrical stimulation (DES). We compared the effects of rIFC stimulation on trials in which responses were made in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 42 publications
(33 reference statements)
10
70
2
Order By: Relevance
“…These regions could be involved in the inhibition of movement induced by the hypnotic suggestion. Indeed, the VLPFC has been associated with motor inhibition in several studies (e.g., see Aron, Robbins, & Poldrack, 2014;Wessel, Conner, Aron, & Tandon, 2013). Stone et al (2007) found the almost exact same region in VLPFC as we did in conversion disorder patients when comparing ''trying to move'' the conversion-paralyzed side with moving the normal control side.…”
Section: A Neural Correlate Of the Intention To Move In The Frontopolsupporting
confidence: 79%
“…These regions could be involved in the inhibition of movement induced by the hypnotic suggestion. Indeed, the VLPFC has been associated with motor inhibition in several studies (e.g., see Aron, Robbins, & Poldrack, 2014;Wessel, Conner, Aron, & Tandon, 2013). Stone et al (2007) found the almost exact same region in VLPFC as we did in conversion disorder patients when comparing ''trying to move'' the conversion-paralyzed side with moving the normal control side.…”
Section: A Neural Correlate Of the Intention To Move In The Frontopolsupporting
confidence: 79%
“…Moreover, longer go trial RTs observed in the active stimulation group support the assumption that this region serves as a Bbrake mechanism^by generally slowing down the response execution (Jahfari et al 2010). Indeed, an earlier study demonstrated that stimulation of the rIFG slowed down responses (Wessel et al 2013).…”
Section: Discussionsupporting
confidence: 61%
“…Effective connectivity measurements have traditionally relied on animal work, but the recent interest in stimulationbased techniques in humans [26][27][28] now provides new data to investigate the influence of directional connectivity on network topology and behaviour. Non-invasive, interventional approaches that make use of transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tDCS) use distant (scalp EEG) or indirect (resting fMRI) measures of neural activity [13,[29][30][31].…”
Section: (D) Importance Of Information Flow In the Brainmentioning
confidence: 99%